Penyuluhan Kesehatan sebagai Upaya Pencegahan Anemia Sejak Dini pada Ibu di Posyandu Kota Tangerang - Kiren Manubulu; Nathalea Layadi; Yona Jane Nanda; Freddy Agamonza (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2026)
Anemia is a health problem that often occurs in women of childbearing age and pregnant women, with a significant impact on individual health and the quality of human resources. This Community Service Activity (PKM) aims to increase the knowledge and awareness of the Lily Posyandu community about anemia through health education accompanied by hemoglobin testing. The activity was carried out on November 18, 2025, with a pre-test and post-test design to assess the effectiveness of the education. A total of 27 participants attended the counseling, which included material delivery, interactive discussions, questionnaire completion, and hemoglobin testing using POCT Hb. The results showed an increase in average knowledge from 76.43% to 95.13%, with a decrease in standard deviation from 30.01 to 6.30, indicating an increase in understanding as well as homogeneity of participants' knowledge. The Wilcoxon test yielded p = 0.043 (p < 0.05), confirming a significant difference before and after the counseling. The greatest improvement occurred in understanding of iron-rich foods, from 11.7% to 94.1%. The leaflet medium proved to support the success of education thanks to its ease of access, simple appearance, and ability to strengthen information retention, despite its limitations compared to audiovisual media. Hemoglobin testing also provided an initial picture of the participants' anemia status. Overall, this PKM activity was effective in improving community health literacy.